Crimes of the future : theory and its global reproduction - Rabaté, Jean-Michel (New York [etc.] : Bloomsbury, 2014)
The decade since the publication of Jean-Michel Rabaté's controversial manifesto The Future of Theory saw important changes in the field. The demise of most of the visible French or German philosophers, who had produced texts that would trigger new debates, then to be processed by Theory, has led to drastic revisions and starker assessments.

Globalization has been the most obvious factor to modify the selection of texts studied. During the twentieth century, Theory incorporated poetics, rhetorics, aesthetics and linguistics, while also opening itself to continental philosophy. What has changed today? The knowledge that we live in a de-centered world has destabilized the primacy granted to a purely Western canon. Moreover, much of contemporary theory remains highly allusive and this is often baffling for students. Theory keeps recycling itself, producing authentic returns of basic theses, terms and concepts. Canonical modern theorists often return to classical texts, as those of Plato, Kant, Hegel, Nietzsche.
Sadržaj: Introduction: Crimes of the Future ; Chapter 1. How global should Theory be? ; Chapter 2. Theory and its lines of flight: Future, Ancient, Fugitive ; Chapter 3. Investigations of a Kantian dog ; Chapter 4. Divided Truths on Lies: Derrida with Hannah Arendt ; Chapter 5. Derrida's anterior futures ; Chapter 6. A Future without death? ; Chapter 7. The No Future of an Illusion ; Chapter 8. The Styles of Theory: Crimes against fecundity ; Chapter 9: Universalism and its limits: the reasons of the absurd ; Chapter 10. After the “Altermodern” ; Conclusion: Laughing at the long-lasting joke of the future (Marx and Kafka, Althusser and Antigone).
Bibliograf, i dr. bilješke uz tekst.
Stvarno kazalo
Keywords: teorija književnosti -- 20. st; filozofija knjževnosti